Identification of Traffic Conflict Technique in Traffic Safety Assessment - Sugasta, Hervian Handika; Adibah, Fairuz; Saputra, Doddy Cahyadi; Santosa, Dimas Puji; Rangga, Boy (Fakultas Teknik Universitas Tanjungpura, 2025)
One of the negative impacts of modern transportation development is the increasing number of traffic accidents, including the rising fatality rates, resulting in serious injuries and loss of life. The low level of traffic safety remains a significant challenge for the government in realising a safe and orderly transportation system. This study aims to identify and categorise the factors that influence the safety level at unsignalized four-legged intersections in Pontianak City. The Research focuses on two intersections: Putri Daranante – Putri Darahitam – Alianyang Street (Intersection 1) and Harapan Jaya – Ampera – Prof. M. Yamin Street (Intersection 2). Data were collected through field surveys using the Traffic Conflict Technique (TCT), based on the Swedish Traffic Conflict Technique and PIARC guidelines. The analysis results indicate that the Time-to-Accident (TA) parameter is the main factor influencing traffic safety levels at both study locations. Intersection 1 exhibited more serious conflict conditions, with TA values ranging from 0.0 to 0.5 seconds and conflicting speeds between 40 and 45 km/h. This study recommends implementing traffic signals and enhancing traffic sign dissemination and enforcement to reduce the number of serious conflicts.